Human gingival mesenchymal stem cells pretreated with vesicular moringin nanostructures as a new therapeutic approach in a mouse model of spinal cord injury. (31st May 2019) - Mammana, Santa; Gugliandolo, Agnese; Cavalli, Eugenio; Diomede, Francesca; Iori, Renato; Zappacosta, Romina; Bramanti, Placido; Conti, Pio; Fontana, Antonella; Pizzicannella, Jacopo; Mazzon, Emanuela
Abstract: Spinal cord injury (SCI) is a neurological disorder that arises from a primary acute mechanical lesion, followed by a pathophysiological cascade of events that leads to further spinal cord tissue damage. Several preclinical and clinical studies have highlighted the ability of stem cell therapy to improve long‐term functional recovery in SCI. Previously, we demonstrated that moringin (MOR) treatment accelerates the differentiation process in mesenchymal stem cells inducing an early up‐regulation of neural development associated genes. In the present study, we investigated the anti‐inflammatory, anti‐apoptotic, and regenerative effects of gingival mesenchymal stem cells (GMSCs) pretreated with nanostructured liposomes enriched with MOR in an animal model of SCI. SCI was produced by extradural compression of the spinal cord at levels T6–T7 in ICR (CD‐1) mice. Animals were randomly assigned to the following groups: Sham, SCI, SCI + GMSCs (1 × 10 6 cell/i.v.), SCI + MOR‐GMSCs (1 × 10 6 cell/i.v.). Our data show that MOR‐treated GMSCs exert anti‐inflammatory and anti‐apoptotic activities. In particular, MOR‐treated GMSCs are able to reduce the spinal cord levels of COX‐2, GFAP, and inflammatory cytokines IL‐1β and IL‐6 and to restore spinal cord normal morphology. Also, MOR‐treated GMSCs influenced the apoptotic pathway, by reducing Bax, caspase 3, and caspase 9 expressions.